Clot resolution after 3 weeks of anticoagulant treatment for pulmonary embolism: comparison of computed tomography and perfusion scintigraphy. Issue 4 (11th April 2013) - van, J.; Douma, R. A.; Kamphuisen, P. W.; Gerdes, V. E. A.; Verhamme, P.; Wells, P. S.; Bounameaux, H.; Lensing, A. W. A.; Büller, H. R.
Summary Introduction Little is known about the natural history of clot resolution in the initial weeks of anticoagulant therapy in patients with acute pulmonary embolism (PE). Clot resolution of acute PE was assessed with either computed tomography pulmonary angiography scan (CT‐scan) or perfusion scintigraphy scan (Q‐scan) after 3 weeks of treatment. Methods This was a predefined safety analysis of the Einstein PE study, including PE patients, randomized to either enoxaparin with vitamin K antagonist (VKA) or rivaroxaban. A similar scan as at baseline was repeated after 3 weeks. The percentage of vascular obstruction (PVO) was calculated on the basis of a weighted semiquantitative estimation of obstruction. Clot resolution was assessed blindly by calculating the relative change after 3 weeks. Results PE was diagnosed in 264 patients with CT‐scan and in 83 with Q‐scan. Baseline characteristics were similar. At baseline, the mean PVO assessed with CT‐scan (PVO‐CT) and the mean PVO assessed with Q‐scan (PVO‐Q) were both 21% (standard deviation [SD] 13%) (P = 0.9). The mean relative decrease in PVO was 71% (SD 33%) for PVO‐CT, and 62% (SD 36%) for PVO‐Q (P = 0.02); complete resolution was observed in 44% (116/264; 95% confidence interval [CI] 38–50%) and 31% (26/83; 95% CI 22–42%) with CT‐scan and Q‐scan, respectively (P = 0.04). No difference in clot resolution between enoxaparin/VKA and rivaroxaban was found. Conclusion In patients with acute PE, only 3 weeks of anticoagulant treatment leads to complete clot resolution in a considerable proportion of patients, and normalization is more often observed with CT‐scan than with Q‐scan.